KEBERHASILAN COLLABORATIVE GOVERNANCE DALAM TATA KELOLA RETRIBUSI PARKIR DI DINAS PERHUBUNGAN KOTA KUPANG - Yoan Lisbeth Be’ni Rihi; veronika boleng kelen (JianE (Jurnal Ilmu Administrasi Negara), 2025)
This study aims to analyze the success of collaborative governance in managing parking levy administration at the Department of Transportation of Kupang City. A qualitative research method was employed, using both primary and secondary data. Data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative analysis based on the collaborative governance theory proposed by Ansell and Gash. The findings indicate that the success of parking levy management is influenced by four main indicators. First, face-to-face dialogue plays a crucial role in strengthening collaboration among stakeholders and improving efficiency and effectiveness in parking services. Second, trust-building is a continuous process that requires commitment to transparency, fairness, and service quality improvement. Third, commitment to the process is a core element in achieving effective and sustainable parking management. Fourth, mutual understanding among stakeholders contributes to a more responsive, efficient, and sustainable parking management system that enhances public welfare and stakeholder satisfaction.